Development of Learning Modules for Welding Techniques of Shield Metal Arc Welding (SMAW) on Manual Arc Welding Engineering Subjects at Vocational schools - Safriwardy, Ferry; Nasrah, Sayni; Wansah, Zul (Universitas Malikussaleh, 2022)
The aims of this study is to produce a valid and feasible learning module for Shield Metal Arc Welding (SMAW) welding techniques. The method used in this study is R & D (Research and Development) using the Borg and Gall models. Researchers carry out research from stages one to six. The technique of collecting data is in the form of distributing questionnaires. The validity of the module was measured based on the results of expert validation, the percentage obtained by material expert validation was obtained a value of 85.49% was in the appropriate category, media expert validation obtained a value of 89.49% was in the very feasible category and the response of class XI students of welding technique was obtained a value of 79, 51% are in the eligible category. Based on the results of the validator's assessment of the module, the module is declared very feasible. Responses are measured based on students' assessment of the products developed. Based on the results obtained from student responses, it shows that this module is declared suitable for use in learning welding techniques.